Uniform multiconductor transmission lines above a dissipative earth : direct FDTD analysis and experimental validation - Van der Merwe, Jaco (Stellenbosch : Stellenbosch University, 2012)
Dissertation Ph.D(Ing) -- University of Stellenbosch, 1998.